The Relationship Between Parenting Styles And Anxiety Levels In Children Aged 3-6 Years During Hospitalization - Dior Manta Tambunan; Febri Theresia Sihaloho (International Journal of Health Engineering and Technology, 2026)
Hospitalization is a stressful experience for children, especially when they have to undergo disruptive procedures, which often cause anxiety that affects the child's physical and mental health. This can create a traumatic experience related to hospitalization. This study aims to identify the relationship between parenting styles and anxiety levels in preschool-aged children during hospitalization. The method used in this study is quantitative with a cross-sectional survey design. A total of 52 children aged between 3-6 years (preschool) who were treated at Private Hospital "X" Medan were selected through a purposive sampling technique. A questionnaire was used as the research instrument. Bivariate analysis was conducted using the non-parametric Spearman's Rho test. The findings of this study indicate a significant relationship between parental parenting styles and preschoolers' anxiety levels during hospitalization. Parenting styles significantly influence preschoolers' anxiety levels during hospitalization. Children who receive supportive, democratic, and affectionate parenting styles tend to have better coping mechanisms, resulting in lower anxiety levels than children with less appropriate parenting styles. It is recommended that further researchers conduct intervention studies to identify parenting patterns and add variables of children's coping mechanisms during hospitalization.